Balanced Scorecard dan Kinerja Perguruan Tinggi - Septia Nengsih, Rinte; Muhammad Hamzah Ramadhan Saragih; Ocen Peraga Yugo; Ramadhanti, Putri; Jayadi, Arohman; Edi Eko Priyono (Journal of Student Research, 2025)
The purpose of this research is to conduct a literature review of previous research on the Balanced Scorecard (BSC) from 2020-2024. BSC as a strategic tool management tool that is widely used by universities to improve the performance of their organizations. This research uses SLR which presents quantitative data on BSC issues and university performance. There are several measurements used, namely journals, variables, and theories as well as the field of science reaserch approach. The study results show 30 articles from accredited national journals and national journals. The topic of college performance is influenced by variables of information technology, quality assurance, financial perspective, growth learning perspective, customer perspective, and internal perspective. The theory used is BSC theory. The fields of accounting, management, public universities and private universities have researched a lot about BSC. Based on BSC measurements that are widely used are financial and customer perspectives. Although the college has successfully implemented BSC, the main challenge faced is the adjustment of key performance indicators and long-term goals of the college. This research provides insights, benefits and constraints in implementing and recommending BSC to improve organizational performance.